2022
DOI: 10.3390/su14127202
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Factors on Children’s Mental Health during Home Quarantine: An Empirical Study in Northwest China

Abstract: (1) Aims: This paper aims to analyze the factors affecting children’s mental health during home quarantine from the perspective of family composition in a specific Chinese context where historically, families are small in size. (2) Methods: Here, 10,210 online questionnaires from 3 junior high schools in Xi’an and Hanzhong from 23 to 27 February 2020, were collected to explore the impact of family factors on children’s mental health in Northwest China during home quarantine based on the ecosystem theory, by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Older children during quarantine stayed at home in front of screens without physical activity and, consequently, without injuries [ 29 ]. On the other hand, preschool children were forced to be inside the house, most of the time without careful supervision, but they kept their playfulness, which led them to inside injuries [ 30 , 31 , 32 ]. A significantly high percentage of children’s accidents was observed in rural/island areas as well as in the suburbs, likely because it is more difficult to supervise children in such conditions compared to supervising the narrow space of an apartment or because children in rural areas are less exposed to social isolation and have a lack of contact with peers, so the accidents were not limited [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older children during quarantine stayed at home in front of screens without physical activity and, consequently, without injuries [ 29 ]. On the other hand, preschool children were forced to be inside the house, most of the time without careful supervision, but they kept their playfulness, which led them to inside injuries [ 30 , 31 , 32 ]. A significantly high percentage of children’s accidents was observed in rural/island areas as well as in the suburbs, likely because it is more difficult to supervise children in such conditions compared to supervising the narrow space of an apartment or because children in rural areas are less exposed to social isolation and have a lack of contact with peers, so the accidents were not limited [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parenting can affect children's mental health by providing warmth to children, protection, good communication, and providing good supervision (Sim et al, 2022). Parents with low education will affect children's health, parents don't teach how to deal with stress, can't control bad emotions (Jin et al, 2022). A father's relationship can affect a child's emotional development in the future, a good father and son relationship is a protective factor that prevents children from experiencing depression in academics, careers, and romantic relationships (Fakhrunnisak & Patria, 2022)…”
Section: Physical Activity At Schoolmentioning
confidence: 99%
“…23 24 A study in Northwest China reported that frequent parent-child communication and better parent-child relationships improve children's psychological status associated with children's home isolation. 25 A study conducted by Liu et al on 5000 Chinese children found that a poor parent-child relationship resulted in depression and anxiety in children during quarantine. 26 While confined together, families have more time to work through difficulties, which may result in better and more meaningful relationships.…”
Section: Open Accessmentioning
confidence: 99%